Because Follower Experience Matters: The Continuance Intention to Follow Recommendation of the Influencer - Dedi I. Inan; Achmad Nizar Hidayanto; Ratna Juita; Adiva Reyhan Puteri; Irene Pixelyne Romauli; B. Putri Kinanti Ramadhani; Taliza Ayu Dwiputritaufik (Human Behavior and Emerging Technologies)
In harnessing social media, for the follower to keep following recommendations from the influencer, the concerns are primarily focused on the influencer side only. However, the follower’s experience, in fact, is equally crucial as, at the end of the day, that is the follower who decides to continue following or not the recommendation from the influencer over all the influences. Therefore, this paper examines the follower experience determining the follower to keep following the influencer’s recommendation. In particular, the psychological aspects imbued by the experience that promotes well-being and inspiration affect the follower’s intention to continue to follow. A total of 292 screened respondents were gathered and analysed. The findings reveal that the psychological factors: emotional design, functionalities, and hedonism perceived by the follower enhance well-being and inspire them to continue following the influencer’s recommendation. Theoretically, this research demonstrates how well-being and inspiration are the determinants and sheds more light on how the follower experience contributes to understanding the continuance intention to follow the influencer’s recommendation. Practically, this research informs the influencer and the brand that understanding the follower experiences is also crucial for more effective influence. The limitation and future research directions are also discussed.